One-Pot Stereoselective Synthesis of Dimethyl-(Z)-2- (ethanimidoylsulfanyl)-2-butenedioate from Dimethyl Acetylendicarboxylate and Thioacetamide in Presence of Zinc Oxide Powder - ARJMANDFAR, HAMID; NAMJOU, NAFISEH; RAMAZANI, ALI (Asian Journal of Chemistry, 2010)
Thioacetamide reacts with dimethyl acetylenedicarboxylate in presence of acetone to form dimethyl (Z)-2-(ethanimidoylsulfanyl)-2-butenedioate. Zinc oxide powder was found to catalyze the reaction in solvent-free conditions at 90ºC in 1 h.